Association of Alternative Approaches to Normalizing Peritoneal Dialysis Clearance with Mortality and Technique Failure: A Retrospective Analysis Using the United States Renal Data System-Dialysis Morbidity and Mortality Study, Wave 2. Issue 1 (January 2017) - Boyle, Suzanne M.; Li, Yimei; Wilson, F. Perry; Glickman, Joel D.; Feldman, Harold I.
Background: Total body water (V) is an imprecise metric for normalization of dialytic urea clearance (Kt). This poses a risk of early mortality/technique failure (TF). We examined differences in the distribution of peritoneal Kt/V when V was calculated with actual weight (AW), ideal weight (IW), and adjusted weight (ADW). We also examined the associations of these Kt/V measurements, Kt/body surface area (BSA), and non-normalized Kt with mortality and TF. Methods: This is a retrospective cohort study of 534 incident peritoneal dialysis (PD) patients from the Dialysis Morbidity and Mortality Study Wave 2 linked with United States Renal Data System through 2010. Using Cox-proportional hazard models, we examined the relationship of several normalization strategies for peritoneal urea clearance, including Kt/VAW, Kt/VIW, Kt/VADW, Kt/BSA, and non-normalized Kt, with the outcomes of mortality and TF. Harrell's c-statistics were used to assess the relative predictive ability of clearance metrics for mortality and TF. The distributions of Kt/VAW, KT/VIW, and KT/VADW were compared within and between body mass index (BMI) strata. Results: Median patient age: 59 (54% male; 72% white; 91% continuous ambulatory PD [CAPD]). Median 24-hour urine volume: 700 mL; median estimated glomerular filtration rate (eGFR) at initiation: 7.15 mL/min/1.73 m 2 . Technique failure and transplant-censored mortality at 5 years: 37%. Death and transplant-censored TF at 5 years: 60%. There were no significant differences in initial eGFR and 24-hour urine volume across BMI strata. There were statistically significant differences in each Kt/V calculation within the underweight, overweight, and obese strata. After adjustment, there were no significant differences in the hazard ratios (HRs) for TF/mortality for each clearance calculation. Harrell's c-statistics for mortality for each clearance calculation were 0.78, and for TF, 0.60 – 0.61. Conclusions: Peritoneal urea clearances are sensitive to subtle changes in the estimation of V. However, there were no detectable significant associations of Kt/VAW, Kt/VIW, Kt/VADW, Kt/BSA, or Kt with TF or mortality.